Serial cranial and spinal cord magnetic resonance imaging in multiple sclerosis. - Wiebe, S; Lee, D; Karlik, S; Hopkins, M; Vandervoort, M; Wong, C; Hewitt, L; Rice, G; Ebers, G; Noseworthy, J (1992)
Twenty-nine mildly disabled patients with multiple sclerosis underwent serial clinical and magnetic resonance imaging (MRI) evaluations (pre- and postgadolinium cranial and spinal cord MRI) on at least 3 occasions at 13-week intervals and during periods of suspected relapse. Using clinical judgment of the presence of recent active disease as the gold standard, combined MRI studies confirmed the clinical impression of active disease in 93% of follow-up visits (sensitivity) and the absence of active MS in 63% of follow-up visits (specificity). None of the cranial and spinal MRI-detected abnormalities disappeared. Gadolinium administration particularly increased the yield of spinal MRI. Cranial MRI alone detected 80% of the MRI-active visits. Clinical and MRI concordance was significantly better for the presence of recent disease activity than for the anatomical localization of the presumed site of activity. MRI evidence of apparent ongoing disease activity was seen more frequently in patients believed to have active multiple sclerosis in the preceding year (13 of 21) than in patients who had been in clinical remission for at least the 2 preceding years (2 of 8). Although clinical evidence of new disease activity was much less common in patients with active, chronic-progressive disease (1 of 8) than in patients with active, relapsing disease (9 of 13), the proportion of patients with either infrequent relapses, frequent relapses, or slow chronic-progressive disease in the preceding year in whom MRI activity developed and the pattern of this new MRI activity was similar between these types of active patients.(ABSTRACT TRUNCATED AT 250 WORDS)